2007
DOI: 10.3844/ajassp.2007.759.767
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Analysis of a CI Engine Performance Using Waste Cooking Biodiesel Fuel with an Artificial Neural Network Aid

Abstract: Abstract:A comprehensive combustion analysis has been conducted to evaluate the performance of a commercial DI engine, water cooled two cylinders, in-line, naturally aspirated, RD270 Ruggerini diesel engine using waste vegetable cooking oil as an alternative fuel. In order to compare the brake power and the torques values of the engine, it has been tested under same operating conditions with diesel fuel and waste cooking biodiesel fuel blends. The results were found to be very comparable. The properties of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 10 publications
1
23
0
1
Order By: Relevance
“…Refaat et al (2008b) found that the difference in performance between microwave-enhanced biodiesel and petroleum diesel was not statistically significant; a slight increase in SFC was detected with biodiesel, no significant differences were observed in brake thermal efficiency and the combustion efficiency remained constant using either microwave-enhanced biodiesel or Diesel fuel. Najafi et al (2007) noticed that by adding 20 % of waste vegetable oil methyl ester to petrodiesel fuel the maximum power and torque increased by 2.7 % and 2.9 %, respectively (Najafi et al, 2007). The same results were reconfirmed in a succeeding study by the authors (Ghobadian et al, 2009).…”
Section: Performance Tests Of Wvo-based Biodieselsupporting
confidence: 72%
See 1 more Smart Citation
“…Refaat et al (2008b) found that the difference in performance between microwave-enhanced biodiesel and petroleum diesel was not statistically significant; a slight increase in SFC was detected with biodiesel, no significant differences were observed in brake thermal efficiency and the combustion efficiency remained constant using either microwave-enhanced biodiesel or Diesel fuel. Najafi et al (2007) noticed that by adding 20 % of waste vegetable oil methyl ester to petrodiesel fuel the maximum power and torque increased by 2.7 % and 2.9 %, respectively (Najafi et al, 2007). The same results were reconfirmed in a succeeding study by the authors (Ghobadian et al, 2009).…”
Section: Performance Tests Of Wvo-based Biodieselsupporting
confidence: 72%
“…The performance of engines fueled with biodiesel produced from waste vegetable oil was extensively covered in the literature (Dorado, 2003a;Tashtoush et al, 2003;Volmajer and Kegl, 2003;Najafi et al, 2007;Lapuerta et al, 2008;Meng et al, 2008;Refaat et al, 2008b;Utlu and Kocak, 2008;Ghobadian et al, 2009) Lapuerta et al (2008 tested two different biodiesel fuels, obtained from waste cooking oils with different previous uses in a diesel commercial engine either pure or in 30 % and 70 % v/v blends with a reference diesel fuel. The main objective of their work was to study the effect of biodiesel blends on particulate emissions, measured in terms of mass, optical effect (smoke opacity) and size distributions.…”
Section: Performance Tests Of Wvo-based Biodieselmentioning
confidence: 99%
“…The use of ANN for the prediction of the cetane number of biodiesel has been presented in [52]. Furthermore, a based prediction of performance and emission characteristics of a variable compression ratio CI engine, using WCO as a biodiesel at different injection times by means of ANN was examined by Shivakumara et al [53], whereas Najafi et al [54] have applied ANN in the performance and exhaust emissions of a biodiesel engine, and Najafi [55] carried out a combustion analysis of a CI Engine Performance employing waste cooking biodiesel fuel with an ANN Aid. Another application includes not only biodiesel production from soybean oil [56] and waste frying palm oil [57], but also the prediction of engine performance for an alternative fuel [58] and the simulation of biodiesel production from waste olive oil [59].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies reported that engine effective power and brake thermal efficiency are lower and brake specific fuel consumption is higher for used frying oil methyl ester and its blends than diesel fuel, especially with increase of biodiesel in the blends (Canakci et al, 2009;Rao et al, 2008;Utlu and Kocak, 2008;Murillo et al, 2007;Sudhir et al, 2007;Dorado et al, 2003;Canakci and Van Gerpen, 2003;Prabhu et al, 2013). However, some studies reported that biodiesel could cause a slightly higher engine effective power than diesel fuel (Deepanraj et al, 2011;Usta et al, 2005;Najafi et al, 2007). These discrepancies can be related to the fact that, the biodiesel has different physical and chemical properties, which depends on the feedstock used to produce it, from those of diesel fuel, which cause changes in engine performance.…”
Section: Introductionmentioning
confidence: 97%